2020
DOI: 10.3390/molecules25143222
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of Modified Atmosphere Packaging and UV-C Radiation on Pathogens Reduction, Biogenic Amines, and Shelf Life of Refrigerated Tilapia (Oreochromis niloticus) Fillets

Abstract: This study investigated the isolated effect of modified atmosphere packaging (MAP; 50% CO2 and 50% N2) and ultraviolet radiation (UV; 0.30 J/cm2) as well as their combined (MAP/UV) effect on reduction of Salmonella typhimurium and Escherichia coli O157:H7, biogenic amines (BA), and on shelf life of tilapia fillets stored at 4 ± 1 °C for 10 days. UV samples had the highest reduction of S. typhimurium (1.13 log colony forming units/g; CFU/g) and E. coli O157:H7 (0.70 log CFU/g). MAP and MAP/UV reduced the growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 74 publications
(147 reference statements)
0
8
0
Order By: Relevance
“…Molina et al (2014) reported some fluctuations in hardness and chewiness; however, they observed, in general, that UVC at 79,000 and 1580 mJ/cm 2 increased these parameters in sea bass fillets stored under refrigeration for 11 days. Lázaro et al (2020) also observed an increase in hardness and chewiness by applying UVC at 300 mJ/cm 2 in tilapia fillets under refrigerated storage for 10 days. Monteiro et al (2020) found that UVC at 102 mJ/cm 2 decreased the hardness and chewiness of refrigerated stored tilapia fillets over 23 days.…”
Section: 4mentioning
confidence: 70%
See 2 more Smart Citations
“…Molina et al (2014) reported some fluctuations in hardness and chewiness; however, they observed, in general, that UVC at 79,000 and 1580 mJ/cm 2 increased these parameters in sea bass fillets stored under refrigeration for 11 days. Lázaro et al (2020) also observed an increase in hardness and chewiness by applying UVC at 300 mJ/cm 2 in tilapia fillets under refrigerated storage for 10 days. Monteiro et al (2020) found that UVC at 102 mJ/cm 2 decreased the hardness and chewiness of refrigerated stored tilapia fillets over 23 days.…”
Section: 4mentioning
confidence: 70%
“…Monteiro et al (2017) observed no effect of UVC light at 103 mJ/cm 2 in b* values of vacuum-packed tilapia fillets stored under refrigeration for 11 days, whereas UVC at 305 mJ/cm 2 increased this parameter. Lázaro et al (2020) reported that UVC at 300 mJ/cm 2 tended to increase b* values of vacuumpacked tilapia fillets over refrigerated storage for 10 days, but no significant difference was found. Molina et al (2014) observed no influence of UVC at 1580 mJ/cm 2 and increased b* values by using 790 mJ/cm 2 in refrigerated stored sea bass fillets for 11 days.…”
Section: Instrumental Color Parametersmentioning
confidence: 92%
See 1 more Smart Citation
“…US alone cannot reduce the microbial count, but combined treatment shows reductions of 3.3 and 1.2 CFU/ml for total mesophilic aerobic bacteria and yeasts and molds, respectively. The treated juice is microbiologically stable for 30 days with higher flavonoid content and little degradation of vitamin C. Likewise, supercritical CO 2 and high‐power USs were applied in chicken breast against mesophilic bacteria and yeasts and molds for 6 log reduction (Morbiato et al., 2019); MAP and UV radiation in tilapia fillets against E. coli O157:H7 and S. typhimurium for 1.13 and 0.7 log reduction (Lázaro et al., 2020); US and plasma‐activated water in chicken meat and skin against S. aureus and E. coli by 0.83 and 1.33 log reduction (Royintarat et al., 2020); ozonated and electrolyzed water in goat meat against E. coli K12 by 1.03 log reduction, aqueous ozone and UVC in beef meat against E. coli by 1.7 log reduction (Perez et al., 2022); organic acid in combination with atmospheric CP (ACP) in poultry meat surface against S. typhimurium by >2.5 log reduction (Yadav & Roopesh, 2022); US and lysozyme in liquid whole egg against S. typhimurium by 4.26 log reduction (Bi et al., 2020). US and ozone in cashew apple juice against total mesophilic aerobic bacteria, yeasts and molds by 3.3 and 1.2 CFU/ml (Fonteles et al.…”
Section: Effective Mitigation Strategies For Food Borne Pathogensmentioning
confidence: 99%
“…Zhang et al [30] investigated the effect of air packaging, vacuum packaging, and MAP (75% CO 2 + 25% N 2 ) on the microbial composition and quality of lightly salted grass carp. Lázaro et al [31] studied the combined effect of MAP (50% CO 2 + 50% N 2 ) and ultraviolet radiation type C (UV-C; 0.30 J/cm 2 ) on the reduction of Salmonella typhimurium and E. coli O157:H7 in tilapia fillets. The impact of Ar and N 2 used individually for MAP on the chemical, sensory, and microbiological qualities of refrigerated Asian sea bass slices was studied by Olatunde et al [32].…”
Section: Introductionmentioning
confidence: 99%